Комплексно-варіативний метод як засіб розвитку фізичних якостей студентів загальних груп НТУ "ХПІ" - Арабаджи, Тимур Дмитрович; Арабаджи, Анна Юріївна; Матузна, Наталя (Прикарпатський національний університет імені Василя Стефаника, 2023)
Розглянуто особливості побудови занять з фізичного виховання студентів загальних груп НТУ "ХПІ" зі спеціалізації "Легка атлетика" з різним рівнем фізичної підготовленості. Було підібрано та впроваджено в навчальний процес комплекси фізичних вправ, які по складності доступні для виконання кожному студенту. Мета. Вивчити та проаналізувати рівень фізичної підготовленості студентів. Розробити, експериментально обґрунтувати та впровадити до навчальної програми комплекси вправ на основі комплексно-варіативного методу. Матеріал і методи дослідження. Були використані: теоретичний аналіз та узагальнення даних науково-методичної літератури; педагогічні методи; аналіз, систематизація та узагальнення; метод математичної статистики. Отримані результати. Комплексно-варіативний метод дозволив якісно підібрати вправи залежно від рівня фізичної підготовленості студентів та водночас підвищити рівень ефективності проведення занять для загальних груп НТУ "ХПІ". Висновки. Впровадження до занять з легкої атлетики комплексно-варіативного методу, в цілому покращило показники фізичної підготовленості студентів.

In this article the authors considered the peculiarities of building classes of physical education of students of general groups of NTU "KPI" specializing in "Athletics" with different levels of physical fitness. A set of physical exercises in the educational process, which would be available to each student, were selected and implemented. The indicators of physical fitness of students were also tested and analyzed in the work. A set of exercises for the classes of the complex-variant method was developed, based on the means and methods of training in athletics. The results of the study indicate an improvement in the training of each individual student with the systematic use of the complex-variative method. Objective. To study and analyze the level of physical fitness of students of general groups of NTU "KPI" specializing in "Athletics". To develop, experimentally substantiate and implement into the curriculum complexes of exercises based on a complex-variative method aimed at improving the physical fitness of students of these groups. Provide recommendations for conducting athletics classes. Material and methods of research. The methods of research that were used to achieve the set goal in the work: theoretical analysis and generalization of scientific and methodological literature data; pedagogical methods; analysis, systematization and generalization; method of mathematical statistics. Obtained results. The complex-variative method allowed qualitatively choose exercises depending on the level of physical fitness of students and at the same time increase the level of effectiveness of classes for general groups of NTU "KPI", which led to the improvement and harmonious development of all physical qualities of students who are specializing in "Athletics". Conclusions. The introduction of a complex-variative method of training in athletics has improved physical fitness of students. Due to the use of this method the educational process was rationally adapted to the study of each student with different level of physical fitness.
Keywords: легка атлетика; фізичне виховання; фізична підготовка; комплексно-варіативний метод; студенти; athletics; physical education; physical training; complex-variative method; students